Being a combat officer in the Army: a transgenerational delegation? - MOLINA, Silvana de Fátima Lima (2012)
The aim of this study was to investigate the influence exerted by a father and Army officer, in deciding if the child will follow a military career and how the child perceives this career. More specifically, it sought to analyze the motivations that led to this decision; the gains achieved and the difficulties in exercising this career; the role of the family and expectations for the future. The study was carried out on twenty student cadets in the Agulhas Negras Military Academy (named for one of the highest mountains in Brazil, literally Black Needles). They responded to an interview that was analyzed in accordance with the technique of Thematic Content Analysis. As the main motivations for this career choice, the results pointed to the strong influence of the father, family support, as well as daily contact with the routine and the rules of the institution. The feeling of pride and honor pervaded all the interviews, although they acknowledged that it is a career that involves loss, sacrifice and constant effort. Expectations of the future relate to the desire for continuous dedication to improving the performance and postings, as well as building a Family